Clinical effects of a one-year cardiac rehabilitation program using physical training after myocardial infarction in patients of working age with different rehabilitation potentials - M. G. Bubnova; D. M. Aronov (Кардиоваскулярная терапия и профилактика, 2019)
Aim. To study the effectiveness of cardiorehabilitation (CR), based on one-year physical training (PT) of moderate intensity, with different levels of rehabilitation potential (RP) in patients of working age after myocardial infarction.Material and methods. The study included 300 patients having myocardial infarction 3-8 weeks ago. All patients were randomized into groups: the main “M” (n=155) for physical rehabilitation and the control “C” (n=145). Each group were divided into three subgroups depending on the level of RP, classified by exercise tolerance (ET) during the load test: high level — ET >100 W, medium >50- ≤100 W and high ≤50 W. Patients underwent PT of moderate intensity 3 times a week during a year. All patients received standard therapy.Results. Under the influence of PT, the power and duration of load increased, respectively, with low RP by 87,5% and 62,2% (p<0,001), average RP by 51,1% and 44,9% (p<0,001), high RP by 13,9% and 15,0% (p<0,001). In the C subgroups, these parameters increased to a lesser extent with a low and medium RP, and significantly increased with a high RP. After PT, in any level of RP, the end-systolic diameter decreased and the ejection fraction of the left ventricle increased. In high RP there was also a decrease in the end-diastolic size. In patients without PT, in contrast, the size of the left atrium increased slightly with low and high RP. After a year of FT, the body mass index decreased with any RP, with higher effect at high RP by 4,6% (p<0,001), in contrast to non-trained patients. Daily motor activity after a year of PT increased, especially with low RP by 28,4% (p<0,05), and in the absence of PT even decreased with low RP by 29,6% (p<0,05). In training patients with any RP, the level of low-density lipoproteins decreased against the background of an increase of high-density lipoproteins. In the absence of PT, triglyceride growth was observed. At any level of RP against PT, the frequency of angina episodes, the number of cardiovascular complications and days of temporary disability decreased, leading to improving of quality of life.Conclusion. The one-year CR program, based on systematic PT of moderate intensity, leads to a positive clinical effect at any level of RP of the patient. Particularly noticeable are the clinical benefits of participating in the CR program and a marked increase in ET in the range of its initially low values in patients with low RP.